Using PdO and PbO as the starting materials to prepare a multi-walled carbon nanotubes supported composite catalyst (PdxPby/MWCNTs) for ethanol oxidation reaction (EOR). (18th January 2018) - Ding, Keqiang; Li, Chenxue; Zhang, Yan; Wang, Li; Wei, Binjuan; Shi, Xiaomi; He, Xiangming
Abstract: For the first time, a novel composite catalyst, namely, a multi-walled carbon nanotubes (MWCNTs) supported palladium and lead catalyst (denoted as Pdx Pby /MWCNTs), was prepared through a hydrothermal method using PdO, PbO and MWCNTs as the starting materials. The electrocatalytic activities of the resultant catalysts towards EOR in 1M KOH were examined mainly by using CV, CA and EIS. The electrochemical measurement results indicated that the peak current of EOR in the forward potential scan on the catalyst of Pd1 Pb1 /MWCNTs was almost 9 times larger, plus about 100 mV decrease in the onset potential value of EOR, than that on the Pb-free catalyst. A very simple, cost-effective and scalable way to synthesize Pd and Pb composite electrocatalyst for EOR was presented in this work, which was very meaningful to the further commercialization of EOR. Highlights: The catalysts of Pdx Pby /MWCNTs have electrocatalytic activity for EOR. The peak current density of EOR on Pd1 Pb1 /MWCNTs is 9 times larger than that on Pb-free catalyst. An evident self-activation is found for the Pb-contained catalyst for EOR.